Code-switching among the indigenous people of Sarawak - Norhuda Salleh; Romlah Ramli; Noor Syakirah Zakaria; Ahmad Faisal Mohamed Fiah (Global Academic Excellence (M) Sdn Bhd, 2022)
As a multicultural country, it is common for Malaysians to have the ability to speak two or more languages. Apart from being proficient in their own native language, majority Malaysians are able to speak Bahasa Melayu or English, or even both. In Sarawak, the indigenous people are collectively known as natives, also referred as the people of Dayak and Orang Ulu. The background of the Sarawak community, where the people itself are multilingual, supports the notion that code-switching is a common occurrence in the community’s daily life. This research aims to find out how the natives accommodate their communication behavior when interacting by identifying the occurrence of code-switching and, the factors and reasons contributing to the phenomenon. The research method uses quantitative methods. The data were collected by distributing questionnaires via Google Form. The findings were analyzed using the Communication Accommodation Theory (CAT) by Howard Giles. Based on the findings, there is a significant relationship between the indigenous ethnic groups in Sarawak and the phenomenon of code-switching. Convergence type of accommodation was observed through the study where the natives accommodate their language as a strategy reduce the social differences between themselves and their interactant. It is also observed that the natives also accommodate their language to achieve a clearer and smoother communication.